Physical performance, heart rate variability and hormone concentrations in cross-country skiers throughout the season - Lajunen, Kimmo (2016)
Cross-country skiing is an extremely demanding and versatile competitive sport. Fairly little is known about changes in basal hormonal concentrations and function of the autonomic nervous system throughout the season. Better understanding about these changes as well as their relationship to changes in physical performance and training could be useful for designing better training practices and periodization. This study followed 22 national level cross-country skiers (12 men, 10 women) throughout one competitive season. They were tested at the beginning of the season, during the general preparation season, during the specific preparation season and after the competition season for physical performance, serum hormone concentrations and heart rate variability. In addition athletes kept training diaries during the whole study period. Physical performance tests included skating roller-skiing VO2max test on a treadmill, maximal double poling speed (DPvmax) on a treadmill, 30-meter double poling, countermovement jump and bench press. Relationships between changes in physical performance, hormone concentrations, heart rate variability and training variables were also analyzed. Time to exhaustion in the VO2max test (100 %, 105 ± 8 %, 107 ± 7 % and 102 ± 10 %,p=0.002)andinDPvmax test(100%,111±14%,121±14%,115±10%,p< 0.001) increased significantly during the season, while VO2max remained unaltered. In addition 1RM in bench press improved significantly (100 %, 103 ± 4 %, 107 ± 8 %, 103 ± 5 %, p < 0.001). Total testosterone (13.7 ± 4.1 nmol/l, 14.0 ± 3.8 nmol/l, 14.7 ± 3.3 nmol/l, 15.2 ± 3.3 nmol/l, p = 0.034) and free testosterone (290 ± 80 pmol/l, 300 ± 79 pmol/l, 314 ± 75 pmol/l, 325 ± 64 pmol/l, p = 0.049) in men increased significantly during the season. Heart rate variability remained unaltered. During the season total (14.0 ± 4.1 h/w, 13.8 ± 2.9 h/w, 10.8 ± 2.6 h/w, p < 0.001) and low-intensity (11.2 ± 3.8 h/w, 11.2 ± 2.8 h/w, 8.7 ± 2.4 h/w, p < 0.001) training volume decreased and high-intensity (0.21 ± 0.26 h/w, 0.25 ± 0.18 h/w, 0.47 ± 0.22 h/w, p < 0.001) and ski-specific (5.0 ± 2.7 h/w, 5.8 ± 1.8 h/w, 7.2 ± 1.9 h/w, p < 0.001) training volume increased. Changes in total testosterone concentration correlated negatively with changes in the time to exhaustion in VO2max test (e.g. between test 1 and 3 r = -0.70, p = 0.001, n = 19). Low-intensity training volume correlated negatively with changes in the time to exhaustion in DPvmax test (e.g. between tests 2 and 4 r = -0.083, p < 0.001, n = 14). The results of the present study suggest that cross-country skiers can improve their skiing performance before the competition season, but can only maintain the performance during the competition season. A significant increase in testosterone concentration might indicate cumulating training load and fatigue, and be associated with decreased performance. A negative relationships between the low-intensity training volume and changes in time to exhaustion in the treadmill roller-skiing tests suggest that lowering the volume or intensity of low-intensity training during the competition season might be beneficial for improving performance.